Women and Religion: A Gender Perspective in Religious Practice - Fauziyah*, Nur Laily; Farisi, Taufiq Al (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2024)
This research explores the dynamics of interactions between women and religion with a focus on gender perspectives in religious practice. Religion often plays an important role in social and cultural life, influencing the norms and values that govern individual behavior in society. However, religious interpretations and practices are often influenced by patriarchal structures that place women in an unequal position compared to men. This study uses a qualitative approach with case study methods and literature analysis to understand how women participate in religious practices and how they respond to existing gender norms. This research spans a range of religious traditions including Islam, Christianity, Hinduism, and Buddhism, and explores variations in women's experiences across different cultural and social contexts. The results show that despite significant challenges and obstacles, women often find ways to articulate their religious identity and participate actively in their religious communities. Some women use religious spaces as platforms to promote gender equality and social justice. In addition, this research reveals significant differences in the way women interpret religious teachings and how they apply them in their daily lives. This research highlights the importance of an interdisciplinary approach in understanding the relationship between gender and religion. Through in-depth analysis, this research contributes to a richer understanding of how women negotiate their religious identities and how they can become agents of change in society.